The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1128/jb.179.17.5318-5320.1997
|View full text |Cite
|
Sign up to set email alerts
|

Role of four major cellulases in triggering of cellulase gene expression by cellulose in Trichoderma reesei

Abstract: The relative contributions of four major cellulases of Trichoderma reesei (1,4-␤-D-glucan cellobiohydrolase I [CBH I], CBH II, endo-1,4-␤-D-glucanase I [EG I], and EG II) to the generation of the cellulase inducer from cellulose were studied with isogenic strains in which the corresponding genes (cbh1, cbh2, egl1, and egl2) had been deleted by insertion of the Aspergillus nidulans amdS marker gene. During growth on lactose (a soluble carbon source provoking cellulase gene expression), these strains showed no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 23 publications
4
30
0
1
Order By: Relevance
“…crassa cellobiohydrolase(I) (CBHI) is the most highly produced extracellular protein during growth on Avicel or Miscanthus, and deletion of this gene causes the most severe growth deficiencies on cellulosic substrates. By contrast, in H. jecorina, deletion of cbhII caused the most severe phenotype (23)(24)(25). In N. crassa, deletion of cellobiohydrolase(II) also causes growth deficiencies on cellulosic substrates, but to a much lesser extent than CBH(I), suggesting that exoglucanase activity in N. crassa is predominantly from CBH(I) and that endoglucanases and other CBHs do not compensate for the loss of CBH(I).…”
Section: Discussionmentioning
confidence: 89%
“…crassa cellobiohydrolase(I) (CBHI) is the most highly produced extracellular protein during growth on Avicel or Miscanthus, and deletion of this gene causes the most severe growth deficiencies on cellulosic substrates. By contrast, in H. jecorina, deletion of cbhII caused the most severe phenotype (23)(24)(25). In N. crassa, deletion of cellobiohydrolase(II) also causes growth deficiencies on cellulosic substrates, but to a much lesser extent than CBH(I), suggesting that exoglucanase activity in N. crassa is predominantly from CBH(I) and that endoglucanases and other CBHs do not compensate for the loss of CBH(I).…”
Section: Discussionmentioning
confidence: 89%
“…Instead, elevated levels of CBHII (approximately twice that of CBHI) were observed (Kubicek et al 1993b). That CBHI and CBHII act as initiators of growth of Trichoderma on cellulose was further supported by the findings that conidia from a cbh1-and cbh2-negative strain were almost unable to initiate growth on cellulose (Seiboth et al 1997). Addition of the cellulase-inducer sophorose to a culture of this deletion strain induced transcription of remaining cellulases such as egl1 and egl2 and restored the ability to attack cellulose.…”
Section: Recognition Of Insoluble Substratesmentioning
confidence: 89%
“…Antibody competition and antisense RNA experiments have led to the proposal that low basal levels of cellulases (mainly Cel7A and Cel6A) are necessary for further induction (5,12). Analysis of CBH gene expression by using cellulase deletion mutants strongly suggested that basal expression of Cel6A and GH family 5 EG (Cel5A) is indispensable for the formation of the inducer(s) of CBHs from cellulose (37,38).…”
mentioning
confidence: 99%